2006
DOI: 10.2337/dc05-2371
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Effect of the Internet-Based Glucose Monitoring System on HbA1c Reduction and Glucose Stability

Abstract: OBJECTIVE -To investigate the long-term effectiveness of the Internet-based glucose monitoring system (IBGMS) on glucose control in patients with type 2 diabetes.RESEARCH DESIGN AND METHODS -We conducted a prospective, randomized, controlled trial in 80 patients with type 2 diabetes for 30 months. The intervention group was treated with the IBGMS, while the control group made conventional office visits only. HbA 1c (A1C) was performed at 3-month intervals. For measuring of the stability of glucose control, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
203
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 184 publications
(208 citation statements)
references
References 32 publications
3
203
0
2
Order By: Relevance
“…For PPG, four studies (16,18,27,28) presented outcome data and the meta-analysis showed a significant reduction in telecare group compared with standard care group from baseline (K52.86 mg/dl; 95% CI, K77.13 to K28.58; P!0.05). There were nine studies (13,16,18,21,23,27,28,29,30) with FPG data that could be pooled to metaanalysis, which indicated a small but significant difference in FPG decline from baseline, favoring telecare intervention (K9.00 mg/dl; 95% CI, K17.36 to K0.64; PZ0.03).…”
Section: European Journal Of Endocrinologymentioning
confidence: 99%
“…For PPG, four studies (16,18,27,28) presented outcome data and the meta-analysis showed a significant reduction in telecare group compared with standard care group from baseline (K52.86 mg/dl; 95% CI, K77.13 to K28.58; P!0.05). There were nine studies (13,16,18,21,23,27,28,29,30) with FPG data that could be pooled to metaanalysis, which indicated a small but significant difference in FPG decline from baseline, favoring telecare intervention (K9.00 mg/dl; 95% CI, K17.36 to K0.64; PZ0.03).…”
Section: European Journal Of Endocrinologymentioning
confidence: 99%
“…Clearly, SMBG may not be useful to patients who lack the necessary skills and motivation. However, several studies that have tested randomised interventions in patients already using SMBG [5,6] found that training to improve their ability to make appropriate behavioural decisions in response to blood glucose readings resulted in better glycaemic control.…”
mentioning
confidence: 99%
“…Available studies of telematics systems applied to diabetes are generally short in follow-up and small in sample sizes. To date, the study that has evaluated over a longest time the usefulness of a glucose monitoring system based on Internet, had a follow-up of 30 months (Cho et al, 2006). It concluded with a significantly greater reduction in HbA1c and a reduction in the rate of fluctuation of HbA1c in the intervention group compared to control.…”
Section: Review Of the Literature: What Has Been Done By Other Researmentioning
confidence: 99%